The role of protein kinase C in the stimulus-secretion coupling in rat parotid gland. - Lin, Wei. (University of Ottawa (Canada), 1992)
The role of protein kinase C (PKC) in stimulus-secretion coupling in a number of endocrine and exocrine tissues remains poorly understood. In this study, the activation of a specific PKC isozyme during cAMP-mediated secretion from rat parotid acini has been examined. Hydroxylapatite chromatography and immunoblotting studies, with a specific antibody against PKC-$\beta$ utilizing a sensitive enhanced chemiluminescence detection system, indicated that the $\beta$ form was the major PKC isoenzyme in rat parotid gland. Isoproterenol (ISO, 0.1 $\mu$m), a $\beta$-adrenergic agonist, stimulated the translocation of PKC-$\beta$ from the cytosolic to the particulate fraction. A time-course study with this agonist showed that total particulate PKC increased from 50% (resting level) to about 80% during 30 minutes of stimulation, accompanied by a decrease from 50% to 20% in the cytosolic distribution. At low concentrations (up to 0.1 $\mu$M), ISO caused significant redistribution of PKC-$\beta$ during 30 min of stimulation in a dose-dependent manner (Kd = 10 nM). The rate of amylase release evoked by ISO (0.1$\mu$M) was linear during 30 minutes, in good correlation with the translocation of PKC-$\beta$ from cytosol membrane. A permeant cyclic AMP derivative (dibutyryl cAMP) also caused the translocation of PKC-$\beta$ in a dose-dependent manner (Kd $\leq$ 50 $\mu$M). Stimulation with the phorbol ester PMA (10 nM, 100 nM) resulted in both PKC translocation and amylase secretion. Total PKC activity was assayed using a specific peptide substrate and yielded a similar pattern of stimulation of PKC translocation in response to these secretagogues. The accumulated evidence suggests that PKC-$\beta$ becomes activated and translocates during $\beta$-adrenergic-stimulated amylase secretion from rat parotid acini. Therefore PKC-$\beta$ activation may be the common pathway for synthesis stimulus-secretion coupling during stimulation by agonists that cause cAMP synthesis or PIP$\sb2$ hydrolysis.
Keywords: Biology, Anatomy.